Das Mausoleum von Belevi Bauforschung - Heinz, Reinhard (6f7036c4-7a43-4a76-89b6-eeb583d841ef, 2017)
The volume presents the concluding architectural and structural research on this early Hellenistic tomb of a Diadochus, a monumental two-story construction with innovative design of building structure, façades and a peristasis, enclosing an unused courtyard. Pure proportions determined the modularly composed design, having been brought to perfection by numerous optical refinements. Innovative developments of construction techniques such as the utilisation of grout mortar indicate the forthcoming era and so do the new formal developments in the design of this mausoleum having grown out of late classical tradition.